Kleisiaris, Christos - (:unkn) unknown (My University, 2026)
I was born in Sarantaporo - a famous village in the region of Central Greece. I am 42 years old and, I live and work in Heraklion of Crete in the last three years. My research activities focus on the elderly population especially in the end of life (4th stage of chronic diseases). Additionally, my recent research focuses on respiratory diseases especially in Chronic Obstructive Pulmonary Disease and Obstructive Sleep Apnoea Syndrome as a result of my PhD.